Chest Sonography - Mathis, Gebhard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
Chest sonography is an established procedure in the stepwise imaging diagnosis of pulmonary and pleural disease. It is the method of choice to distinguish between solid and liquid lesions and allows the investigator to make an unequivocal diagnosis without exposing the patient to costly and stressful procedures. Since the second edition of this book, the value of chest sonography has been further demonstrated in many new studies, especially with respect to the application of portable ultrasound stethoscope systems. The new, third edition of Chest Sonography presents the state of the art in chest investigation by means of ultrasonography and has been updated to take into account the results of the 1st International Consensus Conference on Pleural & Lung Ultrasound. The numerous excellent illustrations and the compact text provide concise and easy-to-assimilate information about the diagnostic procedure. Basic aspects such as indications, investigative techniques, and image artifacts are detailed in separate chapters, and entirely new chapters have been included on emergency ultrasound of the chest and pediatric chest sonography.
Indications, Technical Prerequisites, and Investigation Procedure -- The chest wall. - The Pleura -- Subpleural Lung Consolidations -- Mediastinum -- Endobronchial Sonography:- Vascularization.-Image Artifacts and Pitfalls -- Interventional Chest Sonography -- The White Hemithorax -- From the Symptom to the Diagnosis.-Emergency Ultrasound of the Chest.-Pediatric Chest Sonography.
Keywords: Medicine; Radiology, Medical; Diagnosis, Ultrasonic; Pneumology; Medicine & Public Health; Ultrasound; Imaging / Radiology; Pneumology/Respiratory System